2019
DOI: 10.1038/s41598-019-49957-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effects from four years of industry-led badger culling in England on the incidence of bovine tuberculosis in cattle, 2013–2017

Abstract: The objective was to measure the association between badger culling and bovine tuberculosis (TB) incidents in cattle herds in three areas of England between 2013–2017 (Gloucestershire and Somerset) and 2015–2017 (Dorset). Farming industry-selected licensed culling areas were matched to comparison areas. A TB incident was detection of new Mycobacterium bovis infection (post-mortem confirmed) in at least one animal in a herd. Intervention and comparison area incidence rates were compared in central zones where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…The Krebs Randomized Badger Culling Trial (RBCT) remains the key source of empirical information on this issue; the resulting report concluded that in areas where there was high incidence of bTB there was compelling evidence that badgers were a significant source of infection in cattle 1 . Recent evidence suggests that industry led culling of badgers in England was associated with reductions in cattle TB incidence rates after four years but there were variations in effects between cull areas 7 .…”
mentioning
confidence: 99%
“…The Krebs Randomized Badger Culling Trial (RBCT) remains the key source of empirical information on this issue; the resulting report concluded that in areas where there was high incidence of bTB there was compelling evidence that badgers were a significant source of infection in cattle 1 . Recent evidence suggests that industry led culling of badgers in England was associated with reductions in cattle TB incidence rates after four years but there were variations in effects between cull areas 7 .…”
mentioning
confidence: 99%
“…However, wildlife reservoirs play an important and sometimes unpredictable role in disease transmission to farm animals, e.g., badgers in the UK ( 4 ), possums in New Zealand ( 5 ), or wild boars in Spain ( 6 ). The control of such animal reservoirs can directly influence the prevalence of human TB, as seen in New Zealand ( 7 , 8 ) or the UK ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Badger killing is ineffective. Downs and others1 used mathematical modelling to claim that, up until September 2017, the bovine tuberculosis (bTB) situation in cattle in their studied areas of the Gloucestershire pilot cull zone had improved after four years of culling – and this was much trumpeted as a success story by ministers. However, analysis of subsequent data released by APHA2 demonstrated that both the prevalence and incidence of disease in cattle herds in the Gloucestershire pilot cull zone were higher following five full years of culling than before culling began 3.…”
mentioning
confidence: 99%
“…While incidence had fallen in the Somerset pilot cull zone, prevalence among cattle herds remained static over this period, and in the Dorset pilot cull zone the prevalence increased by 20 per cent over three years of culling. If the analysis performed by Downs and others1 were to be repeated to include the more recent data, very different conclusions would ensue.…”
mentioning
confidence: 99%